The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0100-879x2004001200004
|View full text |Cite
|
Sign up to set email alerts
|

Rarity of DNA sequence alterations in the promoter region of the human androgen receptor gene

Abstract: The human androgen receptor (AR) gene promoter lies in a GC-rich region containing two principal sites of transcription initiation and a putative Sp1 protein-binding site, without typical "TATA" and "CAAT" boxes. It has been suggested that mutations within the 5'untranslated region (5'UTR) may contribute to the development of prostate cancer by changing the rates of gene transcription and/or translation. In order to investigate this question, the aim of the present study was to search for the presence of mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The third alteration ,which was found in the one healthy man out of 100 blood donors, was 25delT in a conserved region of 5 0 -UTR. In the same study no germ-line alterations were found among 92 prostate cancer patients [25]. In addition, one somatic change in 3 0 -UTR of a prostate cancer specimen has been reported [26].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The third alteration ,which was found in the one healthy man out of 100 blood donors, was 25delT in a conserved region of 5 0 -UTR. In the same study no germ-line alterations were found among 92 prostate cancer patients [25]. In addition, one somatic change in 3 0 -UTR of a prostate cancer specimen has been reported [26].…”
Section: Introductionmentioning
confidence: 78%
“…Two single cases of germ-line alterations have been identified in the 5 0 -UTR and one in the promoter region, two of these in prostate cancer patients [24], and one in a healthy male blood donor [25]. The alterations that were found in one prostate cancer patient were G-10T within the ARTIS I and C203A within a GC rich region of the 5 0 -UTR [24].…”
Section: Introductionmentioning
confidence: 97%